2007
DOI: 10.1348/000709906x120132
|View full text |Cite
|
Sign up to set email alerts
|

The effects of selective schooling and self‐concept on adolescents' academic aspiration: An examination of Dweck's self‐theory

Abstract: The findings provide substantial support for Dweck's self-theory, showing that implicit theories are related to aspirations. However, the way in which theory of intelligence relates to age and gender suggests there may be important cross-cultural or contextual differences not addressed by Dweck's theory. Further research should also investigate the causal paths between aspirations, implicit theories of intelligence and the impact of school selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
3
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 50 publications
(63 reference statements)
4
45
3
3
Order By: Relevance
“…Thirdly, the measure of academic achievement in the present study is not strictly based on grades. In some of our research (Ahmavaara & Houston, 2007;Jonsson & Beach, 2012;Shim, Cho, & Cassady, 2013), the achievement outcome was not explicitly stated in the form of grade points, which may result in the ambiguity or the non-normalization of academic achievement to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirdly, the measure of academic achievement in the present study is not strictly based on grades. In some of our research (Ahmavaara & Houston, 2007;Jonsson & Beach, 2012;Shim, Cho, & Cassady, 2013), the achievement outcome was not explicitly stated in the form of grade points, which may result in the ambiguity or the non-normalization of academic achievement to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…A growth mindset predicted a higher achievement through the intermediate variables of goal setting (e.g., performance and learning goals), goal operation (e.g., helpless and mastery-oriented strategy), and goal monitoring (e.g., negative emotion and expectations) (Ahmavaara & Houston, 2007;Fonseca et al, 2009;Leondari & Gialamas, 2002). For example, in…”
Section: Mindset As a Causementioning
confidence: 99%
See 1 more Smart Citation
“…For example, within an academic context, students who believed their intelligence to be a fixed trait viewed negative events such as poor test performance as indicators of inadequacy, which led to negative self-perception judgments (Ahmavaara and Houston 2007). Studies examining a range of populations (e.g., Norwegian, Swedish) and domains (e.g., academics, leadership) identified a link between implicit theories and self-efficacy (Braten and Stromso 2005;Burnette et al 2010) and between implicit theories and self-confidence (Ollfors and Andersson 2007;Stevenson 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The FBP’s effect on academic competence at the 11-month follow-up has not been investigated, but given that the FBP led to improvements in teacher reports of child behavior problems in school, it is plausible to expect that FBP also improved other measures of school functioning at that time point. Research with non-bereaved populations has found that academic self-perceptions predict later academic achievement and occupational goals (Ahmavaara & Houston, 2007; Emmanuelle, 2009; Juang & Silbereisen, 2002). The study expands on previous research in several important ways.…”
Section: Putative Moderators and Mediators Of Fbp Effects On Academicmentioning
confidence: 99%